2012
DOI: 10.1371/journal.pone.0031618
|View full text |Cite
|
Sign up to set email alerts
|

Division of Labor in the Hyperdiverse Ant Genus Pheidole Is Associated with Distinct Subcaste- and Age-Related Patterns of Worker Brain Organization

Abstract: The evolutionary success of ants and other social insects is considered to be intrinsically linked to division of labor among workers. The role of the brains of individual ants in generating division of labor, however, is poorly understood, as is the degree to which interspecific variation in worker social phenotypes is underscored by functional neurobiological differentiation. Here we demonstrate that dimorphic minor and major workers of different ages from three ecotypical species of the hyperdiverse ant gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
99
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(102 citation statements)
references
References 65 publications
1
99
2
Order By: Relevance
“…The CC is being increasingly implicated in integrative functions as well as motor output [54], and maintenance of the OL neuropil with increasing age could be particularly important to extranidal task performance. Pheidole dentata have relatively small eyes and OLs [31] which could contribute to lower levels of redundancy in these circuits and hence greater importance for their protection. High variability in the proportion of apoptotic cells in the CC likely stems from the small number of cells that comprise this region, causing a small absolute change in the number of dying cells to more strongly influence this proportion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The CC is being increasingly implicated in integrative functions as well as motor output [54], and maintenance of the OL neuropil with increasing age could be particularly important to extranidal task performance. Pheidole dentata have relatively small eyes and OLs [31] which could contribute to lower levels of redundancy in these circuits and hence greater importance for their protection. High variability in the proportion of apoptotic cells in the CC likely stems from the small number of cells that comprise this region, causing a small absolute change in the number of dying cells to more strongly influence this proportion.…”
Section: Discussionmentioning
confidence: 99%
“…Mean counts per calyx (lateral or medial) and means of both calyces were analysed with a oneway ANOVA. Counts were converted to MG per mm 3 using calyx neuropil measurements from Muscedere & Traniello [31].…”
Section: (C) Age-related Changes In Neuroanatomy (I) Measurement Of Amentioning
confidence: 99%
See 1 more Smart Citation
“…Using as our proxy for brain size, the volume of brain neuropil less the volume of the measured structure or structures, which we term RB [33], bivariate relationships between the C, OL, AL and AL þ OL volume with brain size were found to be moderate to strong (r 2 range: 0.32-0.97), with log-log SMA slope point estimates ranging from 0.78 to 2.01 (electronic supplementary material, were not (although, in the latter two cases, these did not result in significant deviations from isometry for the combined volume of the AL þ OL).…”
Section: (A) Paper Waspsmentioning
confidence: 99%
“…Even less attention has been given to the scaling of the major primary sensory input neuropils-the antennal (AL) and optic lobes (OL)-which process olfactory and visual afferent information, respectively, and supply the mushroom body calyces (C) in hymenopterans. Understanding how these aspects of brain composition affect worker behaviour and division of labour has been a prominent goal of social insect research, and significant interspecific variation in brain composition associated with task performance has begun to be identified in ants [21,33,47,50] and wasps [51]. Absolute brain size was recently proposed to constrain the evolution of the organization of the functional module comprising the C, AL and OL in polistine wasps [49]; interspecific comparisons suggested that small-brained wasps have lower ratios of C volume to the combined volume of the AL þ OL (C/AO hereafter) owing to positive allometry between C and brain size and negative allometry between AL þ OL and brain size.…”
Section: Introductionmentioning
confidence: 99%